Historical Irony: The Israeli State Is Mostly Endangered by Its Religious Sector - Gurevitz, Michael (European Journal of Applied Sciences, 2024)
The Jewish people (Israelites) suffered thousands of years from invasions and destructions of their Canaan homeland (e.g., Assyria in 721 BC; Babylon in 597 BC; Rome in 63 BC), pogroms during exile (e.g., mostly in the 19th century in Eastern Europe, and even nowadays by the Palestinian terror organization Hamas), and attempts of extermination (e.g., holocaust during World War II; attack by the Arabic states upon the re-establishment of Israel in 1948), but miraculously they survived against all odds.